Cell biology of the trypanosome genome. - Daniels, J; Gull, K; Wickstead, B (2010)
Trypanosomes are a group of protozoan eukaryotes, many of which are major parasites of humans and livestock. The genomes of trypanosomes and their modes of gene expression differ in several important aspects from those of other eukaryotic model organisms. Protein-coding genes are organized in large directional gene clusters on a genome-wide scale, and their polycistronic transcription is not generally regulated at initiation. Transcripts from these polycistrons are processed by global trans-splicing of pre-mRNA. Furthermore, in African trypanosomes, some protein-coding genes are transcribed by a multifunctional RNA polymerase I from a specialized extranucleolar compartment. The primary DNA sequence of the trypanosome genomes and their cellular organization have usually been treated as separate entities. However, it is becoming increasingly clear that in order to understand how a genome functions in a living cell, we will need to unravel how the one-dimensional genomic sequence and its trans-acting factors are arranged in the three-dimensional space of the eukaryotic nucleus. Understanding this cell biology of the genome will be crucial if we are to elucidate the genetic control mechanisms of parasitism. Here, we integrate the concepts of nuclear architecture, deduced largely from studies of yeast and mammalian nuclei, with recent developments in our knowledge of the trypanosome genome, gene expression, and nuclear organization. We also compare this nuclear organization to those in other systems in order to shed light on the evolution of nuclear architecture in eukaryotes.